Dystrybucyjny model odmian społecznych języka - Kiklewicz, Aleksander (Stylistyka, 2021)
The paper presents the critical review of sociolinguistic investigations, in particular in the field of social typology of language variants. The author considers such conflicting problems of sociolinguistic classifications of language changes as the lack of exact use of the notion “the language”, the intersection of different classification criteria and the lack of one way of dividing, contradiction as well as incompleteness of the classification. Some categories of social language distinctness, for example the opposition of written and spoken language, are also objects of criticism. The author arranges the linguistic no- menclature, in particular he introduces two opposite categories: informal language/spe- ech as a functional style and ordinary/colloquial language/speech as one of sociolects. The author proposes his own classification of language variants, which leans on two criteria: subjective or functional proprieties of language variants. In this way, following the example of the natural binary Gray codę, the matrix of language changes is generated, where nine categories can be distinguished. The proposed model of language variants can also be applied to the description of multilingual situations.